Monitoring contractile dermal lymphatic activity following uniaxial mechanical loading. Issue 9 (September 2016) - Gray, RJ; Worsley, PR; Voegeli, D; Bader, DL
Highlights: Human dermal lymphatic flow using fluorescent imaging. Establishment of robust parameters to define lymphatic function. Evidence of lymph vessel damage following uniaxial mechanical loading. Implications in pressure ulcer aetiology. Abstract: It is proposed that direct mechanical loading can impair dermal lymphatic function, contributing to the causal pathway of pressure ulcers. The present study aims to investigate the effects of loading on human dermal lymphatic vessels. Ten participants were recruited with ages ranging from 24 to 61 years. Participants had intradermal Indocyanine Green injections administrated between left finger digits. Fluorescence was imaged for 5 min sequences with an infra-red camera prior to lymph vessel loading, immediately after axial loading (60 mmHg) and following a recovery period. Image processing was employed to defined transient lymph packets and compare lymph function between each test phase. The results revealed that between 1-8 transient events (median = 4) occurred at baseline, with a median velocity of 8.1 mm/sec (range 4.1–20.1 mm/sec). Immediately post-loading, there was a significant ( p  < 0.05) reduction in velocity (median = 6.4, range 2.2–13.5 mm/sec), although the number of transient lymph packages varied between participants. During the recovery period the number (range 1–7) and velocity (recovery median = 9.6 mm/sec) of transient packets were largely restored to basal values. The present study revealed that some individuals present with impaired dermal lymphatic function immediately after uniaxial mechanical loading. More research is needed to investigate the effects of pressure and shear on lymphatic vessel patency.